Penggunaan Bahasa Slang Remaja Dari Masa Ke Masa Di Batam - Suhardianto Suhardianto; Melly Siska Suryani (LPPM Universitas Putera Batam, 2018)
This study aims to find the construction and perspective of the use of Indonesian language slang in Batam from time to time from the 1980s to the 2000s. Data collection methods are observation and interview methods. The technique used is